Construction works for piling system at Infant Jesus Convent School / Mohamad Nur Arif Majid - Majid, Mohamad Nur Arif (2013)
Overall, this report is about deep foundation used at Infant Jesus Convent School to build new block of building consisting on 3 storey canteen and office. The foundation is in category of deep foundation because it use piling for the foundation. The space provided by the school is not wide enough to support three storey building at the site. The project was started from early of January this year (2013) and being targeted to finish the piling works by the end of 2013. Infant Jesus Convent School was placed at the middle of city. And the site provided was located between school buildings. Hydraulic Piling is chosen for the method of piling. Even though this method is high in cost, but the method is not produce noise pollution. The method takes more time than the other piling method, but it works efficiently and environment-friendly.